2010
DOI: 10.5539/jas.v2n2p41
|View full text |Cite
|
Sign up to set email alerts
|

Genetic Polymorphism between Tobacco Cultivar-groups Revealed by Amplified Fragment Length Polymorphism Analysis

Abstract: Tobacco (Nicotina tabacum) has been introduced to Thailand for hundreds of years. All tobaccos cultivated in the country are legally separated to local (or early-imported) and imported cultivar groups. However, no method could precisely differentiate the two groups, especially from cured leaf samples. Amplified fragment length polymorphism (AFLP) analysis was introduced to estimate genetic polymorphism of 19 tobacco cultivars grown in Thailand. Thirty-two selective primer-combinations were screened on the geno… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
1
0
1

Year Published

2011
2011
2018
2018

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 14 publications
(15 reference statements)
1
1
0
1
Order By: Relevance
“…This result was similar to other reports on methylation analysis in Arabidopsis (Cervera et al, 2002) and rice (Ashikawa, 2001). Similar results were also reported in tobacco amplified fragment length polymorphism (AFLP) (Denduangboripant et al, 2010) and SSR analyses. For example, 46 tobacco cultivars from 18 different countries were grouped based on their geographic origins and manufacturing quality traits (Ren and Timko, 2001).…”
Section: Discussionsupporting
confidence: 92%
“…This result was similar to other reports on methylation analysis in Arabidopsis (Cervera et al, 2002) and rice (Ashikawa, 2001). Similar results were also reported in tobacco amplified fragment length polymorphism (AFLP) (Denduangboripant et al, 2010) and SSR analyses. For example, 46 tobacco cultivars from 18 different countries were grouped based on their geographic origins and manufacturing quality traits (Ren and Timko, 2001).…”
Section: Discussionsupporting
confidence: 92%
“…Arslan and Okumus (2006) used RAPD markers in Turkish tobacco germplasm and they also reported that geographically closer populations were present in a single cluster. Denduangboripant et al (2010) used AFLP markers in tobacco and they also found that their studied material showed grouping on the basis of respective geographical regions. The grouping obtained in our study can be supported through this possible assumption, as Samsun Province is considered among the main tobacco-growing areas.…”
Section: Discussionmentioning
confidence: 97%
“…Sejauh ini, daun tembakau diproses secara komersial sebagai bahan utama rokok dan cerutu [5]. Namun demikian, tembakau juga memiliki potensi untuk dikembangkan dalam industri kosmetik [6], bioenergy [7], biopestisida dan industri farmasi [8]. Selain itu, tanaman tersebut juga digunakan sebagai salah satu sistem model yang paling penting dalam pengembangan bioteknologi tanaman [9].…”
Section: Pendahuluanunclassified